The sword and the circle : King Arthur and the knights of the Round Table - Sutcliff, Rosemary; Malory, Thomas, Sir, 15th cent. (New York : Dutton, 1981)
Retells the adventures of King Arthur, Queen Guenevere, Sir Lancelot, and the other knights of the Round Table.
Based chiefly on Sir Thomas Malory's Le morte d'Arthur.
Book Links (A.L.A.).
Wilson's Children.
Wilson's Junior High School.
5.3
5.3
Keywords: Arthur, -- King -- Legends; Arthur, -- King -- Legends; Arthurian romances -- Adaptations; Knights and knighthood -- Folklore; Arthurian romances -- Adaptations; Knights and knighthood -- Folklore